Synergistic therapy for osteoporosis: a soybean osteogenic peptide-loaded fish gelatin/κ-carrageenan gel for enhanced bone regeneration - Gong, Jinpeng; Zhang, Yuhan; Jie, Tao; Huang, Tao; Ma, Yupeng; Chen, Hao; Gan, Jing; Ge, Junbo (Frontiers in Nutrition, 2025)
Osteoporosis is a widespread skeletal disorder associated with reduced bone formation and increased fracture risk. Peptide-based therapeutics offer demonstrate anabolic potential for osteoporosis management but are limited by instability and rapid clearance. In this study, a dual-network hydrogel composed of fish gelatin (FG) and κ-carrageenan (κ-CG) was developed as a biocompatible carrier for a soybean-derived osteogenic peptide (SOP). The FG/κ-CG system exhibited provided mechanical integrity, hydration balance, and thermal stability, thereby enabling sustained peptide protection and controlled release. In a glucocorticoid-induced zebrafish osteoporosis model, oral administration of the SOP-loaded gel effectively restored bone mineralization to a level comparable with alendronate treatment. These findings suggest that the FG/κ-CG-SOP hydrogel provides a stable and bioactive platform for osteogenic peptide delivery and represents a promising nutritional or therapeutic approach for osteoporosis management.